Zentrum und Peripherie : aus sprachwissenschaftlicher Sicht - Zentrum und Peripherie 2016 (2017)
Zentrum und Peripherie (Centre and Periphery) was the main topic of the conference with the same title that was held from 25th to 27th May 2016 at Silesian University in Opava. The gathering of almost 90 experts from nine countries was organized by the Association for German Studies in the Czech Republic together with the Department of German Studies at Silesian University in Opava. The main objective of the conference was to investigate the centre and the periphery of the language from various points of view and provide an overview of new methods and findings in the field of linguistic, literary and didactic research. Within the individual contributions, many questions were posed and many different approaches presented in relation to the given issues, all of which took place in five sections: Centre and Periphery of the German Language, Creation and Analysis of a Language Corpus, Literature Approached Interculturally vs. Transculturally, Canon and Norm in Literature and Didactics of Literature, Error and How to Deal with It.